Farm related and Wild Animals inflicted injuries related to Orthopaedics: Epidemiology and prospects for control (Journal of Nobel Medical College, 2018)
Background : Farm related and wild animals inflicted injuries in Orthopaedics is one of the major concern in developing countries like ours. As we don’t know much about such injuries, it would be landmark study for our country. Therefore, the study helps us know better about its epidemiological aspects.Materials & Methods: This prospective case series of farm related and wild animals inflicted injuries related to Orthopaedics, conducted from May 2006 to April 2008 at Department of Orthopaedics of B P Koirala Institute of Health Sciences, consisting of 87 patients admitted to the Orthopaedic ward, is presented. The preformed structured proforma were used to record the data and, later those records were analyzed.Results : 78 domestic related injuries and 9 wild animal related injuries were recorded in the recruitment period of two year. 23 femoral fractures, 14 humeral fractures, 11 Cervical spine injuries, 10 leg bone fractures, 9 forearm fractures were found. Fall from buffalo, Hit by buffalo were common cause of injuries in domestic related injuries whereas Hit / kick by elephant, attack by bear were causes of wild animal related injuries.Conclusion : This study concluded that all adolescents and adults, of all age group and sex, should be included in community education and intervention programmes for prevention of such injuries. The prevention of this type was necessary.Journal of Nobel Medical CollegeVolume 6, Number 2, Issue 11, July-December 2017, 53-57